(untitled) (Contemporary Central & East European Law, 2024)
One of the key characteristics of administrative law is the diversity of entities acting on behalf of the state and the multitude of areas requiring administrative-legal regulation. As a result, there is also a greater variety of actions taken by parties involved in legal relations than in other branches of law. Contemporary doctrine offers numerous studies dedicated to administrative actions. However, it is important to remember that such dynamic development of this field of research would not have been possible without the contributions of pre-war Polish scholars of administrative law. A particularly notable contribution was made by Stanisław Wincenty Kasznica, who was the first to present and organize a catalog of actions undertaken by the administration. The concept of “administrative action”, proposed by the Professor, can be seen as the first attempt to formulate what has since evolved into the structure that today we refer to as the “form of administrative action”.